Perspectives on Sleep, Sleep Problems, and Their Treatment, in People with Serious Mental Illnesses: A Systematic Review. - Sophie Faulkner; Penny Bee (PLoS ONE, 2016)
Sleep problems are common in people with serious mental illness, and impact negatively on functioning and wellbeing. To understand the development of sleep problems, their maintenance, and their treatment, an in depth understanding of patient perspectives is crucial. A systematic literature review was conducted using Medline, AMED, PsychInfo, Embase and CINAHL. Qualitative and quantitative studies were included if they explored or measured patient perspectives on sleep, sleep problems or sleep treatments in people with serious mental illness. Of the 2,067 hits, only 22 met review inclusion criteria, and high quality evidence was sparse. The limited findings suggested sleep was seen as highly interlinked with mental health. Evaluations of treatments varied, however perceived efficacy and personalisation of treatments were valued. Some evidence suggested patient priorities and conceptualisations regarding sleep may diverge from those of validated screening tools developed in general population and sleep medicine samples. More rigorous research is needed to support adaptation and development of interventions and outcome measures for use in specialist mental health settings. Qualitative studies exploring the experience of sleep disturbance in particular diagnostic groups and contexts are urgently required, as are patient perspectives on sleep interventions.